Prinsip Keadilan dan Musyawarah dalam Hukum Islam Serta Implementasinya dalam Negara Hukum Indonesia - Hariyanto Hariyanto (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2014)
The principle of social justice and the principle of deliberation in the Indonesian state of law are very basic principles. This article proves that, according to Islamic law, justice can be seen from two aspects, legal justice and social justice. Legal justice is closely related to the implementation of law, while social justice is different from the concept of social justice of socialist-communist groups or liberal groups. The concept of social justice is based on the view of social welfare. Meanwhile, the principle of deliberation and consensus is based on the spirit of kinship.